1999
DOI: 10.1177/026839629901400105
|View full text |Cite
|
Sign up to set email alerts
|

Successful is Innovation: The Contingent Contributions of Innovation Characteristics and Implementation Process

Abstract: This paper unifies two apparently competing theories of information systems (IS) implementation by developing a model in which the contributions of innovation characteristics and implementation process theories are contingent upon the implementation context. To do this, we identify the different assumptions regarding the implementation context implicit in the two theories and, based on these differences, develop a contingent model within which to integrate the two theories. A partial test of the model within o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…The purpose is to evaluate the implementation of the concept in terms of usage: participation rate among the ED population, representativeness of the participants, and participation development over time. Usage is the most commonly employed measure of implementation success (Yetton et al, 1999). While usage is not a concern in researcher-controlled situations, because failure to deliver interventions is rare in such situations, measuring completeness of delivery provides crucial information about fidelity of implementation when an intervention practice is implemented by routine staff (Dusenbury et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose is to evaluate the implementation of the concept in terms of usage: participation rate among the ED population, representativeness of the participants, and participation development over time. Usage is the most commonly employed measure of implementation success (Yetton et al, 1999). While usage is not a concern in researcher-controlled situations, because failure to deliver interventions is rare in such situations, measuring completeness of delivery provides crucial information about fidelity of implementation when an intervention practice is implemented by routine staff (Dusenbury et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion process (Fidler and Johnson 1984; Leonard‐Barton 1987; Lin 2008; Rajagopal 2002; Yetton et al . 1999)…”
Section: Conceptualization Of Implementation: Lessons From Other Fieldsmentioning
confidence: 99%
“…Leadership Jeyaraj et al (2006) found that top management support was one of the best predictors of individual IT adoption. Yetton et al (1999) argued that lack of support from top management affects successful implementations. Gallivan (2001) found that clear and strong signal of top management support facilitate all stages of innovation assimilation.…”
Section: Gap Examples Of Relevant Studiesmentioning
confidence: 99%
“…Within the ERP implementation literature, top management support has been repeatedly listed as one of the most critical success factors for ERP implementation efforts (Nah et al, 2001;Aladwani, 2001;Akkermans and Van Helden, 2002). It has also been argued that the lack of support signals from top management may reduce the chances of a successful implementation (Yetton et al, 1999).…”
Section: Mandatory and Voluntary Use In Ta Literaturementioning
confidence: 99%